2019
DOI: 10.12965/jer.1836486.243
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability responses to a combined exercise training program: correlation with adiposity and cardiorespiratory fitness changes in obese young men

Abstract: Although the influence of adiposity indices and cardiorespiratory fitness (CRF) on heart rate variability (HRV) has been demonstrated extensively, the causal link between the changes in adiposity as well as in CRF and the alterations in cardiac autonomic function is unclear. Thus, this study aimed to assess the correlation between the changes in adiposity and CRF and the alterations in HRV after 12-week exercise training. Twenty obese sedentary men aged 20.5±1.2 years were randomly assigned into 2 groups (n=10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
(66 reference statements)
3
23
0
Order By: Relevance
“…Nevertheless, the fact that research shows that the measures of resting HRV were not affected by exercise in the middle-aged group (50–59 years old) compared to the young group [ 26 , 28 ], that changes in HRV indices appear to flatten after 12 weeks of exercise [ 27 ] and that the maintenance of those changes could be achieved by exercising regularly [ 26 ], could in part explain i) the lack of evidence of association between measures of HRV indices and variables from the aerobic capacity test in this study and ii) the conflicting results reported in the literature. Another possible explanation is the newly reported results by Phoemsapthawee et al [ 38 ], showing that changes in vagal-related HRV are related to individual ability to adapt to exercise. This was further confirmed by the multiple stepwise regression, which did not show a meaningful relationship between measures of HRV indices and changes in VO2 peak [ 38 ].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, the fact that research shows that the measures of resting HRV were not affected by exercise in the middle-aged group (50–59 years old) compared to the young group [ 26 , 28 ], that changes in HRV indices appear to flatten after 12 weeks of exercise [ 27 ] and that the maintenance of those changes could be achieved by exercising regularly [ 26 ], could in part explain i) the lack of evidence of association between measures of HRV indices and variables from the aerobic capacity test in this study and ii) the conflicting results reported in the literature. Another possible explanation is the newly reported results by Phoemsapthawee et al [ 38 ], showing that changes in vagal-related HRV are related to individual ability to adapt to exercise. This was further confirmed by the multiple stepwise regression, which did not show a meaningful relationship between measures of HRV indices and changes in VO2 peak [ 38 ].…”
Section: Discussionmentioning
confidence: 97%
“…Another possible explanation is the newly reported results by Phoemsapthawee et al [ 38 ], showing that changes in vagal-related HRV are related to individual ability to adapt to exercise. This was further confirmed by the multiple stepwise regression, which did not show a meaningful relationship between measures of HRV indices and changes in VO2 peak [ 38 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent smaller-sized study demonstrated that a 12-week aerobic exercise intervention was associated with a higher proportion of HF, lower LF component and therefore, lower LF/HF ratio in young men with obesity. 35 The authors concluded that changes of the vagal-related HRV parameters were related to body fat loss in the intervention group compared to the control group. Based on our results, it seems that not only obesity, but also low PA has adverse effects on autonomic nervous system activity.…”
Section: Cardiovascular Risk Profile and Heart Rate Variabilitymentioning
confidence: 98%
“…Overweight individuals had sympathovagal imbalance due to increased sympathetic activity associated with visceral fat [4]. Physical activity significantly reduced adiposity rates and improved HRV variables related to vagal modulation in sedentary obese individuals [21].…”
Section: Introductionmentioning
confidence: 99%